2018
DOI: 10.1016/j.compbiomed.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction prediction in structure-based virtual screening using deep learning

Abstract: We introduce a deep learning architecture for structure-based virtual screening that generates fixed-sized fingerprints of proteins and small molecules by applying learnable atom convolution and softmax operations to each molecule separately. These fingerprints are further non-linearly transformed, their inner product is calculated and used to predict the binding potential. Moreover, we show that widely used benchmark datasets may be insufficient for testing structure-based virtual screening methods that utili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…We compared the results of DEEPScreen with five other deep learning based DTI prediction methods that represent the current state-of-the-art (please refer to the Introduction section) by employing the same datasets used in the corresponding studies. For this analysis, we re-trained and tested DEEPScreen using the exact same experimental settings and evaluation metrics that were described in the respective articles [28][29][30][31][32] . A total of 3 different benchmark datasets were employed for this purpose (please refer to the Methods section).…”
Section: State-of-the-art Dnn-based Methods Performance Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the results of DEEPScreen with five other deep learning based DTI prediction methods that represent the current state-of-the-art (please refer to the Introduction section) by employing the same datasets used in the corresponding studies. For this analysis, we re-trained and tested DEEPScreen using the exact same experimental settings and evaluation metrics that were described in the respective articles [28][29][30][31][32] . A total of 3 different benchmark datasets were employed for this purpose (please refer to the Methods section).…”
Section: State-of-the-art Dnn-based Methods Performance Comparisonmentioning
confidence: 99%
“…The term "deep learning" (DL) is coined for the novel ML techniques that perform significantly better compared to conventional classifiers especially in the fields of computer vision and natural language processing, mainly due to multiple layers of data abstraction 25 32 . The field of the deep learning based DTI prediction is still in its infancy and the studies published so far were mostly focused on the applicability of deep learning algorithms and prototyping 27,28,30,32 . The results of these studies have indicated that deep learning has a great potential to advance the field by identifying unknown DTIs at large-scale [28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…[44] Gonczarek, A., et al develop deep learning architecture for structure-based virtual screening by atom convolution and softmax operation. [45] These studies suggested that DNN were capable of QSAR modeling, and indicated the potential ability of virtual screening. However, DNN's ability to screen large compound libraries has not been tested.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, deep learning has been applying to drug discovery [20], [21]. It has achieved superior performance compared to traditional machine learning techniques in many problems in drug development such as drug visual screening [22], [23], drug-target profiling [24], [25], [26], [27], drug repositioning [28], [29]. Especially in the drug response problem, deep learning is utilized to automatically learn genomic features of cell lines and the structural features of drugs to predict anticancer drug responsiveness [30], [31], [32], [33].…”
Section: Introductionmentioning
confidence: 99%